An empirical model for solvation based on surface site interaction points. Issue 39 (16th September 2021) - Reynolds, Derek P.; Storer, Maria Chiara; Hunter, Christopher A.
Abstract : A rule-based approach for assignment of Surface Site Interaction Points (SSIP) based on the chemical structure of a molecule provides a straightforward spreadsheet method for accurate calculation of solvation free energies. Abstract : Surface site interaction points (SSIP) provide a quantitative description of the non-covalent interactions a molecule makes with the environment based on specific intermolecular contacts, such as H-bonds. Summation of the free energy of interaction of each SSIP across the surface of a molecule allows calculation of solvation energies and partition coefficients. A rule-based approach to the assignment of SSIPs based on chemical structure has been developed, and a combination of experimental data on the formation of 1 : 1 H-bonded complexes in non-polar solvents and partition of solutes between different solvents was used to parameterise the method. The resulting model is simple to implement using just a spreadsheet and accurately describes the transfer of a wide range of different solutes from water to a wide range of different organic solvents (overall rmsd is 1.4 kJ mol −1 for 1713 data points). The hydrophobic effect as well as the properties of perfluorocarbon solvents are described well by the model, and new descriptors have been determined for range of organic solvents that were not accessible by direct investigation of H-bond formation in non-polar solvents.